Anteecology and seed biology of false chestnut (Aesculus hippocastanum L) (Eurasian Scientific Herald, 2023)
This article provides information on the antecology and seed biology of the false chestnut (Aesculus hippocastanum L), the formation of seeds enclosed in a longitudinal fruit capsule, and its biological structure and benefits for human life.